1994
DOI: 10.1111/j.1365-3032.1994.tb01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Antennal glands in Psylliodes chrysocephala, and their possible role in reproductive behaviour

Abstract: Abstract. The antennal morphology of Psylliodes chrysocephala L. (Coleoptera: Chrysomelidae), an important pest of oilseed rape (Brassica napus), was studied. Two types of tricellular, integumentary glands were found. The common antennal glands are distributed under all sensilla‐bearing parts of male and female antennae. The male‐specific antennal glands are only located under a glabrous area found on antennomeres 6–10 of male beetles. The common antennal glands are synthetically active in both pre‐ and post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…This discovery was brought on mostly by studies on the male antennae, functionally related with mating behavior (Dahms 1984, Bin andVinson 1986). Later, antennal glands were also described from several families of Hymenoptera, including Terebrantia (Bin et al 1999b, Isidoro and Bin 1995, Isidoro et al 1996, 1999, Battaglia et al 2002 and Aculeata (Isidoro et al 2000, 2003, 2006, as well as from other insect orders (Bartlet et al 1994, Weis et al 1999, Giglio et al 2005, with different biological significance. In some groups of egg parasitoids, antennal glands can be associated with both males and females specialized antennomeres, as well as closely associated with peculiar sensory structures.…”
Section: Antennal Glands In Egg Parasitoidsmentioning
confidence: 95%
“…This discovery was brought on mostly by studies on the male antennae, functionally related with mating behavior (Dahms 1984, Bin andVinson 1986). Later, antennal glands were also described from several families of Hymenoptera, including Terebrantia (Bin et al 1999b, Isidoro and Bin 1995, Isidoro et al 1996, 1999, Battaglia et al 2002 and Aculeata (Isidoro et al 2000, 2003, 2006, as well as from other insect orders (Bartlet et al 1994, Weis et al 1999, Giglio et al 2005, with different biological significance. In some groups of egg parasitoids, antennal glands can be associated with both males and females specialized antennomeres, as well as closely associated with peculiar sensory structures.…”
Section: Antennal Glands In Egg Parasitoidsmentioning
confidence: 95%
“…Besides Hymenoptera, antennal glands have been described in a few other insect orders (Skilbeck and Anderson, 1994;Weis et al, 1999;Giglio et al, 2005;Belcari and Kozánek, 2006), as well as the presence of the male antennal glands associated with courtship behaviour (Medvedev and Pavlov, 1988;Bartlet et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Free (1956), working with honey bees, showed that the antennae could act as releasers of specific behaviors through contact. However, in some insects, e. g. beetles (Bartlet et al, 1994) the antennae also support glands. In the lower Hymenoptera, i. e. the Parasitica, several different glands located on certain segments of the antennae have been described for a number of species Romani et al, 1999;Isidoro et al, 1999).…”
Section: Introductionmentioning
confidence: 99%